Write Around Strategy Upshot Upon Students’ Writing Skill Competence - Tawali Tawali (Cordova Journal : languages and culture studies, 2020)
The aim of study was to find out the effect of Write Around Strategy towards students’ writing skill in descriptive text. This study applied quantitative method with experimental study type. The technique of collecting the data of the study was using Pre-test and Post-test. The data analysis technique used median, mode and mean to find the effect of student`s writing skill in descriptive text. Based on the explanation above, the researcher concluded that Write Around Strategy was positive effect towards students` writing skill in descriptive text. Based on the data analysis, the researcher found that the result of t- test was 5.92 and the level of 0.05 (9,5), then t-table 200. Therefore, write around strategy were accepted. This meant that the null hypothesis (Ho) which said, “Write Around Strategy has no positive effect towards students’ writing skill in descriptive text.” was rejected, while the alternative hypothesis (Ha) which said, “Write Around Strategy Write Around Strategy has positive effect towards students` writing skill in descriptive text” was accepted.